Application of Titanium Dioxide as an Anti-Bacterial: Mini Review - Suhardin , Suhardin; Zulkarnain, Muh Aryo (Science Tech Group, 2024)
This mini-review discusses the application of Titanium Dioxide (TiO2) as an antibacterial agent, particularly in the context of its use in paint formulations for buildings in tropical climates. The increasing demand for durable and hygienic building materials necessitates innovative solutions that not only enhance aesthetics but also provide self-cleaning and antibacterial properties. TiO2, a semiconductor with photocatalytic capabilities, generates reactive radicals upon exposure to sunlight, effectively degrading organic pollutants and bacteria on surfaces. While TiO2-based coatings have shown promise, challenges such as poor UV stability limit their long-term efficacy. The review highlights recent advancements in modifying TiO2 to improve its photocatalytic performance and durability, suggesting that future research should focus on integrating these coatings with new technologies for broader applications in environmental remediation. By addressing these limitations, TiO2 can play a crucial role in sustainable building practices and public health improvements.